1999
DOI: 10.1002/(sici)1096-9071(199903)57:3<269::aid-jmv10>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Herpesvirus saimiri as a potential human gene therapy vector

Abstract: Herpesvirus saimiri has characteristics that make it amenable to development as a gene therapy vector. The viral genome is thought to be capable of accommodating large quantities of heterologous DNA while the virus itself can infect many different cell types. Virus infection has been shown in many cases to be persistent by virtue of episomal maintenance in the target cell. In this article we examine the ability of nonselectable recombinant viruses expressing the beta-galactosidase gene product to infect a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…Although we have previously demonstrated low levels of virus production at early times after infection in a wide variety of human cell lines transduced with HVS, 36 we were unable to detect any evidence of lytic virus growth in persistently infected Jurkat cells using a sensitive virus recovery assay. In addition, no transcripts of an abundant IE gene could be detected in the cell.…”
Section: Discussioncontrasting
confidence: 76%
“…Although we have previously demonstrated low levels of virus production at early times after infection in a wide variety of human cell lines transduced with HVS, 36 we were unable to detect any evidence of lytic virus growth in persistently infected Jurkat cells using a sensitive virus recovery assay. In addition, no transcripts of an abundant IE gene could be detected in the cell.…”
Section: Discussioncontrasting
confidence: 76%
“…We and others have previously demonstrated that HVS can infect a wide range of human cell lines and that the HVS genome persists in a latent episomal state that segregates to progeny upon cell division allowing longterm in vitro gene expression. [7][8][9][10][11] More recently, we demonstrated that the HVS genome can persist in human tumor xenografts derived from ex vivo HVS-infected human carcinoma cells. 12,19 Our previous work has demonstrated that HVS-based vectors (expressing GFP) persisted as nonintegrated episomes in vivo, and provided long-term transgene expression with no evidence of promoter silencing, viral spread or cytopathic effects.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 More recently, HVS recombinants have been produced expressing beta-galactosidase or enhanced green fluorescence protein (EGFP), and the neomycin resistance genes under the control of the IE CMV and SV40 promoters, respectively. [8][9][10] Analysis using these viruses, which can be grown to a high titer in the permissive owl monkey kidney (OMK) cell line, has demonstrated infection of a wide variety of human carcinoma cell lines at approaching 100% efficiency.…”
mentioning
confidence: 99%
“…This analysis was performed on COS-7 cells infected with HVS strain A-11. COS-7 cells were used because of their ease of culture and because they are fully permissive for HVS infection (Stevenson et al, 1999). COS-7 cells were infected with HVS for 24 h at an m.o.i.…”
mentioning
confidence: 99%